THE RELATIONSHIP OF CHOREOGRAPHY PREPARATION AND ARTISTRY IN AEROBIC GYMNASTICS - I. V. Sokolova (Science and Innovation Center Publishing House, 2015)
Examines the impact choreography training in sports aerobics on artistic skills. Objective to investigate whether the use of funds choreo-graphy in training athletes involved in sports aerobics, to find the relationship between choreographic training and asses-sment for artistry. Method or methodology of work methods of studying the theoretical ski works of scientific content, analysis and processing of scientific texts. The results revealed the relationship between estimates for artistry and means-you dance training in sports aerobics. The scope of the results, the materials may be used by coaches in sports aerobics, for further research on the problem of constructing workout.